Implementasi Sistem Rain Harvesting untuk Meningkatkan Akses Air Bersih di Daerah Terdampak Kekeringan - Mario Zaky Ramadhan; Widdya Hananta Herlambang; Wisnu Jati Nugroho; Muhammad Rafli Ramadhani; Surya Wijaya; Gaizka Rabbani Riady (Yayasan Sagita Akademia Maju, 2026)
The clean water crisis due to drought in Sumberpinang Village, Pakusari District, Jember Regency has caused 141 families to experience difficulties in accessing clean water every dry season, forcing them to travel up to 1.5 kilometers to fetch water. This community service program aims to provide a sustainable solution through the implementation of a rain harvesting system that utilizes rainwater as a water reserve. The implementation method includes field surveys, mapping using Geographic Information Systems (GIS), participatory construction of 3 rain harvesting units with a capacity of 1,100 liters per unit, socialization through Focus Group Discussions (FGD), and evaluation of storage potential based on rainfall data from 2013-2023. The results show that the rain harvesting system has great potential to collect rainwater up to 6,168 liters per month from a 15 m² roof area during the rainy season, which can be utilized as a reserve during the dry season. This program is expected to reduce the physical burden on communities in searching for water and serve as a pilot model for independent replication in other areas facing similar problems.